Problematika Sosial Dalam Bertamu Perspektif Adat Jawa - Putra, Mainsyah; Yamani, Zaki (Al Mabhats : Jurnal Penelitian Sosial Agama, 2023)
Abstract: This research provides an in-depth analysis of the socio-cultural issues associated with the traditional Javanese practice of hospitality. The central problem addressed in this study is the evident alterations and challenges within this traditional practice, which pose potentially threaten the continuity of the inherent cultural values and traditions. The primary objective of this study is to scrutinize and comprehend the transformations in social norms, behaviors, and values within the traditional Javanese hospitality practice and to identify the social factors that influence these changes. The study utilizes a qualitative research methodology, employing a case study approach. Data was assembled through comprehensive interviews with key informants, including traditional leaders and members of the Javanese community who actively engage in the traditional hospitality practice, among others. Data analysis was implemented using an inductive approach, identifying emergent patterns, themes, and concepts within the collected data. The findings indicate that the socio-cultural issues ingrained in the traditional Javanese hospitality practice encompass a loss of awareness and understanding of Javanese customs, a shift in values within the hospitality practice, and the influence of socio-cultural changes that can potentially modify this practice. The declining awareness about Javanese customs has led to a decrease in the practice of traditional hospitality and a shallow understanding of its intrinsic meaning and values. The shift in values within the traditional hospitality practice can be attributed to the impact of external factors such as modernization, urbanization, and globalization. The implications of this research highlight the significance of initiatives aimed at the preservation and revitalization of the traditional Javanese practice of hospitality.   Abstrak: Penelitian ini menganalisis problematika sosial dalam bertamu perspektif adat Jawa. Masalah penelitian ini adalah adanya perubahan dan tantangan dalam praktik bertamu adat Jawa yang dapat mengancam keberlangsungan tradisi dan nilai-nilai budaya yang terkandung di dalamnya. Tujuan penelitian ini adalah untuk menganalisis dan memahami pergeseran nilai-nilai, norma, dan perilaku sosial dalam praktik bertamu adat Jawa serta faktor-faktor sosial yang mempengaruhinya. Metode penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui wawancara mendalam dengan informan kunci yang merupakan tokoh adat, anggota masyarakat Jawa yang masih mempraktikkan bertamu adat, dan pihak terkait lainnya. Analisis data dilakukan dengan menggunakan pendekatan induktif, dengan mengidentifikasi pola-pola, tema, dan konsep-konsep yang muncul dari data yang dikumpulkan. Hasil penelitian menunjukkan bahwa problematika sosial dalam bertamu adat Jawa meliputi hilangnya kesadaran dan pemahaman tentang adat Jawa, pergeseran nilai-nilai dalam praktik bertamu, serta pengaruh perubahan sosial dan budaya yang dapat mengubah praktik ini. Hilangnya kesadaran tentang adat Jawa mengakibatkan penurunan dalam praktik bertamu adat dan pemahaman yang dangkal tentang makna dan nilai-nilainya. Pergeseran nilai-nilai dalam praktik bertamu adat juga terjadi akibat adanya pengaruh dari faktor-faktor eksternal, seperti modernisasi, urbanisasi, dan globalisasi. Implikasi Penelitian berimplikasi terhadap pentingnya upaya pelestarian dan pemulihan praktik bertamu adat Jawa.